2018
DOI: 10.7213/1981-4178.2018.16004
|View full text |Cite
|
Sign up to set email alerts
|

Parasitos gastrointestinais em Puma concolor, Puma yagouaroundi e Leopardus pardalis (Carnivora: Felidae) na Floresta Nacional de Três Barras, SC, Brasil

Abstract: Parasitos ocorrem praticamente em todos os níveis tróficos e sua transmissão geralmente pode depender da presença de hospedeiros intermediários, paratênicos e definitivos dentro de um ecossistema. Entretanto, altas densidades de parasitos nos indivíduos podem expandir os danos em populações e ocasionar endemias. O presente estudo analisou a fauna parasitária a partir de exames coproparasitológicos de Puma concolor, Puma yagouaroundi e Leopardus pardalis, de material coletado em trilhas da Floresta Nacional de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“… Herpailurus yagouaroundi , Santa Catarina, Brazil, Wrublewski et al . (2018). Lagidium wolffsohni , Santa Cruz, Argentina, Fugassa (2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Herpailurus yagouaroundi , Santa Catarina, Brazil, Wrublewski et al . (2018). Lagidium wolffsohni , Santa Cruz, Argentina, Fugassa (2014).…”
Section: Resultsmentioning
confidence: 99%
“… Puma concolor , Santa Catarina, Brazil, Wrublewski et al . (2018). Tolypeutes matacus , Chaco region, Argentina, Ríos (2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, helminths were more frequent than protozoa in the faeces from carnivores. High frequencies of helminths have also been observed in stool samples from carnivores in Thailand, Mexico, Bolivia and Brazil [ 16 , 18 – 29 ]. In this study, the high frequency of helminths showed that the environment inhabited by the animals presented conditions that were favourable for maintenance of nematode, cestode, trematode and acanthocephalan life cycles.…”
Section: Discussionmentioning
confidence: 99%